LITERATUR REVIEW: PEMBERIAN PEGAGAN (CENTELLA ASIATICA) SEBAGAI MINUMAN ALTERNATIF UNTUK MENURUKAN TEKANAN DARAH PADA LANSIA - Islami, Ica Maulina Rifkiyatul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Hypertension usually occurs in people of middle age and above. Causes there are several such things as, changes in the structure of blood vessels, narrowing the lumen, blood vessel becoming stiffer and reduced elasticity. As a result, the risk of developing hypertension increases with age. Treatment of hypertension involves the use of medications and changes in lifestyle habits. Medications for hypertensive patients can be both pharmaceutical and non-pharmacological. The medicinal plant has the ability to reduce high blood pressure by reducing triglyceride levels in the blood, making it a non-pharmacological treatment choice for hypertension. An alternative to non-pharmacological treatment for those with hypertension is the traditional medicine made from the peppermint plant. The method used in this study is literature review. Writing is done through article search by entering keywords in Google Schoolar, Science Direcct, PubMed, and Elsevier. The keywords used in the search are Pegagan, Centella asiatica, blood pressure, Hypertension. In 5 journals results mentioned leaves of peppermint can lower blood pressure. Where the shape of the preparation of pegagan leaves varies, that is, in the form of rebusan, juice, tea or a mixture of tea leaves pegagan with other herbs.